Medical student electives and learning outcomes for global health: A commentary on behalf of the UK Medical Schools Elective Council. (April 2014) - Hastings, Adrian; Dowell, Jon; Eliasz, Michael Kalmus
<x xml:space="preserve">Abstract</x> Background: Electives have the potential to have a very positive impact on the professional development of medical students. Education about issues in global health is widely regarded as a neglected area in the undergraduate curricula of many medical schools. Linking learning outcomes for global health to the elective offers a possible solution that avoids adding additional teaching to crowded courses. Conclusion: This commentary advocates caution as many potential learning outcomes are better addressed elsewhere and setting detailed outcomes erodes the essence of the elective – student choice.